THE IMPLEMENTATION OF 'TYPOMAN GAME' TO TEACH VOCABULARY (Descriptive Qualitative Research) - kholil, mahmud (LPPM Universitas Pekalongan, 2024)
Mastery of English vocabulary is crucial for high school students' communication skills and academic success. However, some students in Indonesia face challenges in mastering English vocabulary, primarily due to a lack of exposure during their elementary school years. Therefore, this research aims to investigate the implementation of the edutainment game